Divergence, gene flow and the origin of leapfrog geographic distributions: the history of color pattern variation in Phyllobates poison-dart frogs - Márquez, Roberto; Linderoth, Tyler; Mejía-Vargas, Daniel; Nielsen, Rasmus; Amézquita, Adolfo; Kronforst, Marcus (Dryad, 2019)
The geographic distribution of phenotypic variation among closely related
populations is a valuable source of information about the evolutionary
processes that generate and maintain biodiversity. Leapfrog distributions,
in which phenotypically similar populations are disjunctly distributed and
separated by one or more phenotypically distinct populations, represent
geographic replicates for the existence of a phenotype, and are therefore
especially informative. Phyllobates poison frogs. We found evidence for
high levels of gene flow between neighboring populations but not over long
distances, indicating that gene flow between populations exhibiting the
central phenotype may have a homogenizing effect that maintains their
similarity, and that introgression between “leapfroging” taxa has not
played a prominent role as a driver of phenotypic diversity in
Phyllobates. Although phylogenetic analyses suggest that the leapfrog
distribution was formed through independent evolution of the peripheral
(i.e. leapfrogging) populations, the elevated levels of gene flow between
geographically close populations poise alternative scenarios, such as the
history of phenotypic change becoming decoupled from genome-averaged
patterns of divergence, which we cannot rule out. These results highlight
the importance of incorporating gene flow between populations into the
study of geographic variation in phenotypes, both as a driver of
phenotypic diversity and as a confounding factor of phylogeographic
inferences.
This repository contains 10 folders, each corresponding to a different
section of the paper's analyses. Within each folder is a text file
detailing the how each analysis was performed.
Keywords: Phyllobates aurotaenia; spatial population genetics; Dendrobatidae; Convergent evolution; Phyllobates terribilis; Phyllobates lugubris; Phyllobates vittatus; Phyllobates bicolor; spatial population genetics; Convergent evolution; Dendrobatidae; aposematism